The grave thief - Hahn, Dee (Puffin Canada, 2022)
Twelve-year-old Spade digs up the graves of the recently deceased and steals their jewels to support his family. One day, his father comes up with a plan to rob a grave in the Wyndhail castle cemetery, but Spade and his brother are caught. Spade is given a second chance as a royal spy and sent on a mission to find the master of the Woegon, a deadly creature that is stalking the castle by night. He soon meets Ember, the queen's niece, and they join forces to learn the truth about the mystery of the legendary Deepstones. They discover the Deepstones have a connection to the Woegon, the queen, a missing king, and the mysterious pebble Spade finds in the Wyndhail cemetery.